The impact of different conservation soil tillage and nitrogen fertilization on wheat grain infection with Fusarium sp - Vrandečić, Karolina (Array, 2019)
The effect of different conservation soil tillage (CST) treatments and different level of nitrogen fertilization on Fusarium wheat grain infection on two locations are presented in this paper. The research was conducted on winter wheat with different soil tillage treatments: conventional tillage to 30 cm depth, subsoiling to 35-40 cm depth, chiselling up to 25 cm, disk-harrowing to 10-15 cm and no-tillage, without any tillage treatments and three different nitrogen rates (N1 - amount reduced by 30% of recommended; N2 - according to standard recommendation and N3 - amount increased by 30% of recommended). The occurrence of Fusarium species was determined in all the tested variants of tillage and fertilization treatments. The effect of reduced fertilization (N1) on Fusarium sp. grain infection in all tillage treatments was statistically lower in comparison with other (N2 and N3) nitrogen treatments. The lowest percentage of wheat grains infected with Fusarium sp. was recorded in conventional tillage on location Magadenovac and no tillage treatments on location Cacinci.